2022
DOI: 10.1111/ecog.06183
|View full text |Cite
|
Sign up to set email alerts
|

Spatial confounding in Bayesian species distribution modeling

Abstract: 1) Species distribution models (SDMs) are currently the main tools to derive species niche estimates and spatially explicit predictions for species geographical distribution. However, unobserved environmental conditions and ecological processes may confound the model estimates if they have direct impact on the species and, at the same time, they are correlated with the observed environmental covariates. This, so‐called spatial confounding, is a general property of spatial models and it has not been studied in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Finally, this simulation did not assess the performance of any of the methods on spatially structured covariates. In such cases, the issue of spatial confounding (Mäkinen et al, 2022) may present itself as a potential issue, affecting inferential properties such as coverage probabilities and Type I errors of the regression coefficients βj, due to collinearity between the spatially structured covariate and spatially structured basis functions/latent variables. This issue would have affected all methods tested in this simulation (except the spatially independent stacked SDM), although its severity would be specific to the precise model setup; see also our discussion in Appendix D.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, this simulation did not assess the performance of any of the methods on spatially structured covariates. In such cases, the issue of spatial confounding (Mäkinen et al, 2022) may present itself as a potential issue, affecting inferential properties such as coverage probabilities and Type I errors of the regression coefficients βj, due to collinearity between the spatially structured covariate and spatially structured basis functions/latent variables. This issue would have affected all methods tested in this simulation (except the spatially independent stacked SDM), although its severity would be specific to the precise model setup; see also our discussion in Appendix D.…”
Section: Resultsmentioning
confidence: 99%
“…a temporal trend or habitat change as in our two case studies), confounding is minimized due to the added temporal component of multi-season data. We have found that recent guidelines for minimizing spatial confounding and understanding its effects in spatially explicit SDMs are applicable to SVC SDMs (Mäkinen et al, 2022), although further research is needed to understand when such confounding may occur and how to best mitigate it.…”
Section: Discussionmentioning
confidence: 99%
“…A more extreme option would have been to leave spatial latent effects out also from the model fitting and explain variation in species' log intensity solely with environmental variables. However, such non‐spatial model would have returned overly optimistic uncertainties to model estimates and not necessarily improved estimates' accuracy (Mäkinen et al., 2022). Moreover, the model structure chosen here corresponds to state‐of‐the‐art SDMs, introduced e.g.…”
Section: Discussionmentioning
confidence: 99%
“…citizen science, data integration, INLA, range prediction, sampling bias, spatial latent effect, Trochilidae relevant covariates (Hawkins et al, 2007;Kim, 2021;Mäkinen et al, 2022). In earlier integrated SDMs which have focused on relatively narrow spatial extents, the risk of such spatial confounding was relatively small (Gelfand & Shirota, 2019;Simmonds et al, 2020), but a recent study showed that spatial confounding impacted the covariate effect estimates already on a country wide extent (Renner et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation